Pengaruh Service Quality dan Customer Relationship Management (CRM) terhadap Customer Loyalty yang dimediasi Customer Satisfaction - Aifa Savira Nur Aini; Surpiko Hapsoro Darpito; A. Y. N. Warsiki (LPPM Institut Bisnis dan Informatika Kesatuan, 2022)
This study aims to determine and analyze the effect of service quality and customer relationship management on customer loyalty mediated through customer satisfaction. This research was a survey research with the data collection is a questionnaire. The population in this study are customers who use IndiHome fixed broadband services in the Special Region of Yogyakarta. The data used in this study is primary data obtained from the answers of 130 respondents with purposive sampling method. The data analysis method used is PLS (Partial Least Square) with the help of the SmartPLS for Windows application version 4. The results showed that: 1) Service Quality has a positive and significant effect on Customer Satisfaction, 2) Customer Relationship Management has a positive and significant effect on Customer Satisfaction , 3) Service Quality has a positive and significant effect on Customer Loyalty, 4) Customer Relationship Management has a positive and significant effect on Customer Loyalty, 5) Customer Satisfaction has a positive and significant effect on Customer Loyalty, 6) Customer Satisfaction mediates a positive and significant influence on service relationships Quality on Customer Loyalty, 7) Customer Satisfaction mediates a positive and significant influence on the relationship between Customer Relationship Management and Customer Loyalty.